2014
DOI: 10.1158/0008-5472.can-13-3014
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Sleep Accelerates Tumor Growth and Progression through Recruitment of Tumor-Associated Macrophages and TLR4 Signaling

Abstract: Fragmented sleep (SF) is a highly prevalent condition and a hallmark of sleep apnea, a condition that has been associated with increased cancer incidence and mortality. In this study, we examined the hypothesis that SF promotes tumor growth and progression through pro-inflammatory TLR4 signaling. In the design, we compared mice that were exposed to SF one week before engraftment of syngeneic TC1 or LL3 tumor cells and tumor analysis three weeks later. We also compared host contributions through the use of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 46 publications
4
139
0
1
Order By: Relevance
“…Moreover, 30 days of IH lead to an increased number and volume of pulmonary metastases when compared to control mice (123). A similar study protocol using epithelial lung tumour cells also showed increased rates of cancer progression in IHexposed animals (124), while other OSA-related factors, such as sleep fragmentation, have similarly been shown to accelerate tumour growth in murine IH models (125).…”
Section: Cancer and Osa In Animal Models And Clinical Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, 30 days of IH lead to an increased number and volume of pulmonary metastases when compared to control mice (123). A similar study protocol using epithelial lung tumour cells also showed increased rates of cancer progression in IHexposed animals (124), while other OSA-related factors, such as sleep fragmentation, have similarly been shown to accelerate tumour growth in murine IH models (125).…”
Section: Cancer and Osa In Animal Models And Clinical Studiesmentioning
confidence: 76%
“…As mentioned above, animal models of sleep fragmentation lead to increased tumour progression; the potential immunological mechanisms behind this will be discussed below (125). Sleep disruption and restriction seen in shift workers are also associated with an increased risk of cancer incidence (134), but specific data examining the relationship between sleep fragmentation per se and cancer are lacking (135).…”
Section: Sleep Fragmentation and Increased Sympathetic Drivementioning
confidence: 99%
“…Various pathophysiologic pathways have been postulated as possible causes of cancer or its increased aggressiveness, and also of greater resistance to antitumoral treatment in the presence of both intermittent hypoxia (IH) and sleep fragmentation (both inherent to sleep apnea). Thus far, these biological hypotheses have been supported by various experimental studies in animals (8,9).…”
Section: Spontaneous Tumorigenesis Induced By Intermittent Hypoxia Inmentioning
confidence: 82%
“…[1][2] However, the adverse effects of perturbed sleep, a much more prevalent condition, as illustrated by unrefreshing sleep, SF, or sleep discontinuity have only recently gained attention as potentially underlying important modulatory effects on biological pathways involved in tumor growth and invasion. 3 In this context, evidence of altered innate immunity by SF that involved TLR4-mediated pathways was apparent, and promoted accelerated proliferation and invasiveness of syngeneic murine tumor models. 3 Recent studies have implicated reactive oxygen species (ROS) in general, and NADPH oxidases (Nox) in particular, as playing dual and divergent roles in oncological processes.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this context, evidence of altered innate immunity by SF that involved TLR4-mediated pathways was apparent, and promoted accelerated proliferation and invasiveness of syngeneic murine tumor models. 3 Recent studies have implicated reactive oxygen species (ROS) in general, and NADPH oxidases (Nox) in particular, as playing dual and divergent roles in oncological processes. The generation of ROS following activation of Nox is not only tightly regulated, but is further coupled with a spatiallyrestricted compartmentalization of ROS, thereby warranting the specificity of the Nox enzymes in cellular and sub-cellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%